Acute Pain with Loss of Shoulder Movement: Multidisciplinary Health Approach - Subramanian, S. S. (Achievements and Challenges of Medicine and Medical Science Vol. 12, 2025)
Painful conditions remain the most common clinical scenario, a challenge indeed for healthcare professionals. An analysis of trauma, infection, systemic conditions, drug, age, gender, patho anatomy, and functional needs of the patients requires multidisciplinary assessment and due intervention with subject-specific evidenced investigation and treatment using clinical reasoning shall enhance patients' early recovery to function. Loss of function with acute pain in the shoulder can to a larger extent limit self-care leading to dependency on disability various causes of pain, and movement limitations on a subject were analyzed and duly treated by medical experts followed by the functional needs of the patient by a physiotherapist. The prognosis was analysed and an evidenced presentation was made on the importance of multidisciplinary care by diabetologist, gynaecologist, orthopaedic surgeon, neurologist and physiotherapist of how shoulder function can be restored conservatively. This novel team approach can facilitate greater quality of health care and an early functional betterment of patients. Findings with scientific evidence in this line can enrich academicians, clinicians and researchers with their practice.